Dihydroartemisinin is potential therapeutics for treating late-stage CRC by targeting the elevated c-Myc level - Xianjing Hu (Nature Publishing Group, 2021)
Abstract Currently, no frontline treatment is effective for the late-stage colorectal cancer (CRC). Understanding the molecular differences in different stages of CRC can help us to identify the critical therapeutic targets for designing therapeutic strategy. Our data show that c-Myc protein is highly expressed in late-stage CRC when compared with early-stage CRC in both clinical samples and in cell lines representing different cancer stages. Given that c-Myc is a well-known oncogenic driver in CRC, its high expression in the late-stage CRC may represent a critical therapeutic target for treating the cancer. Dihydroartemisinin treatment significantly increases c-Myc protein degradation and hence reduces its expression in CRC. The treatment also reduces CRC cell viability. Interestingly, dihydroartemisinin exhibits a more potent growth-inhibitory effect in late-stage CRC than the early-stage CRC. The treatment also possesses potent growth-inhibitory effects in mouse models bearing c-Myc-overexpressed CRC. The reduced c-Myc level and its reduced transcriptional activity reduce the expressions of acetyl-CoA carboxylase, fatty acid synthase, carnitine–palmitoyltransferase-1, and medium-chain acyl-CoA dehydrogenase in the cancer cells. Lipidomics study also shows that dihydroartemisinin treatment changes the metabolic phenotypes in CRC, reduces oxygen consumption, respiration, and ATP production, hence reduces the cell proliferation and induces apoptosis. Our study provides strong pharmacological evidence to support the translation of dihydroartemisinin for the treatment of late-stage CRC by targeting c-Myc.